Songs to revitalise community solidarity among the indigenous Mah Meri of Malaysia - Chan, Clare Suet Ching (Cambridge University Press, 2023)
Mah Meri musicians in Malaysia are calling for a revitalisation of community solidarity by adding fragments of new song text to their traditional songs. Intrinsic to the new song texts are narratives of working together, sharing and unity in the community. Through a reexamination of my personal interviews and fieldnotes with these musicians over the past two decades, I posit that their new song texts address social issues that emerged as the village adopted values of modernisation introduced by policies to integrate these people into mainstream society. Rather than outwardly protesting these policies, I argue that Mah Meri musicians challenge top-down hegemonies through a subtle approach of metaphor, rhetoric, and sympathetic appeal in their songs. They direct their efforts inward to their community to rejuvenate and sustain their indigenous values of egalitarianism.